Creating, grading, and using virtual assessments strategies for success in the K-12 classroom - Maxlow, Kate Wolfe; Sanzo, Karen; Maxlow, James R. (An Eye on education book, 2022)
"This book provides a variety of strategies for creating, grading, and using assessments in the virtual setting. With more teaching and learning taking place online, teachers are adjusting their strategies for creating, grading, and using virtual assessments. This strategies-based book helps you understand the key challenges and solutions to delivering virtual assessments, including use of quizzes, digital worksheets, grading, preventing cheating, and considerations of equity, quality, choice, and efficiency. Designed so that you can pick it up and start reading from any chapter, this book covers topics such as: how to create, grade, and use traditional forms of assessment in the virtual space; how to leverage discussion for meaningful learning in the virtual classroom; how to create, grade, and use virtual performances and projects; digital tools that may be helpful in engaging with and assessing students in the virtual environment. Based on research and full of practical examples, this book guides educators, professional learning teams, and whole schools in implementing a successful virtual assessment plan for all types of intended learning objectives"--